Logical Foundations of Computer Science : International Symposium, LFCS 2020, Deerfield Beach, FL, USA, January 4-7, 2020, Proceedings /: International Symposium, LFCS 2020, Deerfield Beach, FL, USA, January 4-7, 2020, Proceedings. (2020) - Unknown
No abstract available